2004
DOI: 10.1063/1.1652248
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy of transition-metal doped diluted magnetic semiconductors Zn1−xMxO

Abstract: We have investigated the electronic structure of Zn1−xMxO (M: 3d transition metal) by x-ray absorption spectroscopy. Using configuration–interaction cluster-model analyses, electronic structure parameters have been deduced and their chemical trend is discussed. Results show that the p–d exchange constant Nβ is negative and large in cases of Mn, Fe, and Co, which is consistent with the enhancement of magnetic circular dichroism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 23 publications
8
26
0
Order By: Relevance
“…Energy positions and intensities of multiplet features are in good agreement with previous measure-ments of Zn 1−x Co x O ͑x = 0.011-0.054͒ and calculated Co 2p XAS spectra of a Co 2+ ion in a tetrahedral cluster ͑based on the configuration-interaction cluster model͒. 10,11 This suggests that the majority of Co dopants reside at the Zn sites ͑for all Co concentrations͒ and that they are tetrahedrally coordinated with the ligand O atoms. Therefore the magnetic properties of the samples investigated most likely arise from the hybridization between ligand O 2p orbitals and localized Co 3d orbitals in the substitutional sites.…”
Section: Methodssupporting
confidence: 87%
“…Energy positions and intensities of multiplet features are in good agreement with previous measure-ments of Zn 1−x Co x O ͑x = 0.011-0.054͒ and calculated Co 2p XAS spectra of a Co 2+ ion in a tetrahedral cluster ͑based on the configuration-interaction cluster model͒. 10,11 This suggests that the majority of Co dopants reside at the Zn sites ͑for all Co concentrations͒ and that they are tetrahedrally coordinated with the ligand O atoms. Therefore the magnetic properties of the samples investigated most likely arise from the hybridization between ligand O 2p orbitals and localized Co 3d orbitals in the substitutional sites.…”
Section: Methodssupporting
confidence: 87%
“…The properties were similar to the typical II-VI magnetic semiconductors [11,19]: the absorption due to d-d transition of Mn ion, the large magnetoresistance at low temperature, and the spin glass magnetic behavior. Figure 1 shows Photoemission spectroscopy revealed that Mn-doped ZnO had much larger p-d exchange constant [24], and X-ray absorption spectroscopy also confirmed the large p-d exchange constant for Mn-, Fe-, and Co-doped ZnO [25]. These results are consistent with their large MCD.…”
Section: Introductionsupporting
confidence: 78%
“…The most important difference is that the overall amplitude of the exciton splitting is one order of magnitude smaller than the one expected for the value of the p-d exchange energy suggested by the Schrieffer-Wolf theory, 29,30 N 0 β = −3.1 ± 0.1 eV or implied by x-ray spectroscopy, N 0 β = −3.0 eV (Ref. 31). By a quantitative interpretation of the reflectivity spectra, it has been possible to find out how to link these puzzling results to a structure of the valence band in ZnO and to the strong p-d hybridization, expected for materials with the short anion-cation distance.…”
Section: Discussionmentioning
confidence: 97%